The Indigenous People of Biafra's (IPOB) Self-Determination Movements and the Role of the United Nations. - Princewilliams Odera Oguejiofor (JPW (Jurnal Politik Walisongo), 2024)
This study examines “The Dynamics of Self-Determination Movements and the Role of the United Nations: A Case Study of the Indigenous People of Biafra (IPOB) in Nigeria.” The UN's lack of action and formal recognition of IPOB's agitation has undermined the protection of the rights of indigenous people in Nigeria, particularly the Igbo community. The study adopts a qualitative methodology, utilising a time-series research design and documentary analysis of credible secondary sources, including international NGO reports and UN documents. The theoretical framework employed is the Theory of Social Constructivism, which posits that the actions of states and international organizations are shaped by socially constructed norms, ideas, and identities. One key finding is that the UN's indifference can be attributed to complex political dynamics, member states' economic interests, and the prioritisation of territorial integrity over self-determination claims. It is recommended, inter alia, that the UN establish an independent commission or a special rapporteur to investigate allegations of human rights violations against IPOB members and the Igbo community, and hold the Nigerian government accountable for any violations.